Pregnancy outcomes in women with primary ovarian insufficiency in assisted reproductive technology therapy: a retrospective study - Sun, Bo; Li, Lu; Zhang, Yile; Wang, Fang; Sun, Yingpu (Frontiers in Endocrinology, 2024)
Purpose This study aims to retrospectively estimate cumulative reproductive outcomes in women with primary ovarian insufficiency (POI) in assisted reproductive technology (ART) therapy. Methods A total of 139 patients diagnosed with POI were reviewed in this study. Firstly, they were divided into two groups according to oocyte origin: using their own oocytes (OG group) or accepting oocyte donations (OD I group). Secondly, the patients were split depending on the pregnancy outcome. In the OG group, nine patients decided to use others’ oocytes after a failure of attempting to use their own, and this population was the oocyte donation II group (OD II group). Results There were 88 patients who used their own oocytes, while 51 patients accepted oocyte donations. In the OG group, there are only 10 (7.2%) patients who got pregnant, and patients in the OD group had worse hormone levels (FSH 71.37 ± 4.18 vs. 43.98 ± 2.53, AMH 0.06 ± 0.04 vs. 1.15 ± 0.15, and AFC 0.10 ± 0.06 vs. 1.15 ± 0.15) and more years of infertility (5.04 ± 0.48 vs. 3.82 ± 0.30), which explained why they choose oocyte donation. In all the three groups, baseline characteristics were comparable between pregnant women and non-pregnant women. Of the 10 pregnant patients in the OG group, four of them used luteal-phase short-acting long protocol and had pregnancies successfully in their first cycles. Conclusion Ovarian stimulation in POI women requires more cost and time. For those with a stronger desire to have genetic offspring, luteal-phase short-acting long protocol may help them obtain pregnancy rapidly.